2018
DOI: 10.4025/actascibiolsci.v40i1.41512
|View full text |Cite
|
Sign up to set email alerts
|

<b>Filamentous fungi producing enzymes under fermentation in cassava liquid waste

Abstract: The conversion of agroindustrial residues by microorganisms has been explored from fermentative processes to obtain several bioactive molecules. The objective of this work was to isolate and select filamentous fungi present in cassava liquid waste for the production of amylase, carboxymethylcellulose (CMCase), pectinase and xylanase using the same residue as induction substrate in fermentative processes. A total of 65 filamentous fungi were isolated and qualitative tests indicated that approximately 86% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(22 reference statements)
0
0
0
Order By: Relevance
“…The residue generated by the manioc processing can then be used as a substrate for enzyme production, as reported by Gusmão et al (2018), where the authors observed the capacity of fungal strains isolated from their own manipulation to produce enzymes of economic interest. The maximum production of pectinase, xylanase, amylase and CMCase was observed for the species: Aspergillus sp.…”
Section: Introductionmentioning
confidence: 88%
“…The residue generated by the manioc processing can then be used as a substrate for enzyme production, as reported by Gusmão et al (2018), where the authors observed the capacity of fungal strains isolated from their own manipulation to produce enzymes of economic interest. The maximum production of pectinase, xylanase, amylase and CMCase was observed for the species: Aspergillus sp.…”
Section: Introductionmentioning
confidence: 88%